Studies on floral morphology in different genotypes of Jasminum sambac - KALAIYARASI, A; DHANANJAYA, M V; NAIR, SUJATHA A; KUMAR, RAJIV; YOGEESHA, H S; MUNIKRISHNAPPA, P M; DEVAPPA, V; PAVITHRA, S (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was undertaken to study the floral morphology behavior among 22 genotypes of Jasminum sambac. Results revealed that among the different genotypes, cluster bearing habit in terminal position was recorded in genotypes Iruvatchi and IIHR JS - 5, whereas other genotypes recorded forked cymes of cluster flowers in terminal and axillary. Three different shapes of flower bud was recorded among the genotypes, viz. pointed and long, pointed and short, rounded and short. Flower bud colour and colour on flower bud opening was white (155 B or 155 C) and pink tinge on flower bud was recorded in IIHR JS - 5. Star and round shaped flower was observed among different genotypes. Three different types of flowers were recorded, viz., single, double and multi-whorled (3 to 6). Among 22 genotypes, Arka Aradhana recorded longest bud (3.85 cm) and corolla (2.11 cm). The genotype IIHR JS - 5 recorded the longest corolla tube (2.29 cm) and Iruvatchi recorded maximum number of forks per cyme (14). Maximum number of calyx lobe was recorded in Gundumallige (8.79 cm), whereas longest calyx lobe was recorded in Soojimalli (1.49 cm). Bigger size of flower was recorded in Soojimalli (4.64 cm) and maximum number of petals was observed in IIHR JS - 1 (40). The information generated on floral morphological traits in different genotypes will facilitate the planned crop improvement programmes in jasmine.